1997
DOI: 10.1073/pnas.94.13.7076
|View full text |Cite
|
Sign up to set email alerts
|

The AP2 domain of APETALA2 defines a large new family of DNA binding proteins in  Arabidopsis

Abstract: APETALA2 (AP2) plays an important role in the control of Arabidopsis f lower and seed development and encodes a putative transcription factor that is distinguished by a novel DNA binding motif referred to as the AP2 domain. In this study we show that the AP2 domain containing or RAP2 (related to AP2) family of proteins is encoded by a minimum of 12 genes in Arabidopsis. The RAP2 genes encode two classes of proteins, AP2-like and EREBP-like, that are defined by the number of AP2 domains in each polypeptide as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
447
2
11

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 624 publications
(476 citation statements)
references
References 53 publications
9
447
2
11
Order By: Relevance
“…The EREBP/AP2 motif contains an 18-amino acid core region that has been proposed to form an amphipathic ␣-helix; such a secondary structure has been implicated in proteinprotein interactions to facilitate DNA binding (Okamuro et al, 1997). However, the present binding studies cannot determine whether Tsi1 binds to the GCC box or the DRE/CRT box as a monomer or some form of multimer.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…The EREBP/AP2 motif contains an 18-amino acid core region that has been proposed to form an amphipathic ␣-helix; such a secondary structure has been implicated in proteinprotein interactions to facilitate DNA binding (Okamuro et al, 1997). However, the present binding studies cannot determine whether Tsi1 binds to the GCC box or the DRE/CRT box as a monomer or some form of multimer.…”
Section: Discussioncontrasting
confidence: 41%
“…Also, many experiments have shown that certain types of transcription factors required cofactor(s) or post-translational modification for their activation potential and DNA binding properties in plants (Despres et al, 2000; Gu et al, 2000). It is thus possible that Tsi1 may require post-translational modification or a putative cofactor for its function in response to osmotic stress.The EREBP/AP2 motif contains an 18-amino acid core region that has been proposed to form an amphipathic ␣-helix; such a secondary structure has been implicated in proteinprotein interactions to facilitate DNA binding (Okamuro et al, 1997). However, the present binding studies cannot determine whether Tsi1 binds to the GCC box or the DRE/CRT box as a monomer or some form of multimer.…”
contrasting
confidence: 41%
“…For instance, an APETALA2 (AP2)-like protein (HT160) maps coincident with QTLs controlling flowering time and achene size ( Table 2). AP2 is a floral homeotic gene, and AP2 and AP2-like proteins play important roles in the control of flower and seed development (Okamuro et al 1997;Maes et al 2001;Aukerman and Sakai 2003;Faris et al 2003). Likewise, a putative cell division control protein (HT189) colocalizes with QTLs affecting relative growth rate, leaf area, stem diameter, and height, whereas the bZIP transcription factors HT087 and HT179 are associated with stem and leaf size, and achene and disk size QTLs, respectively (Table 2).…”
Section: Possible Functions Of Estsmentioning
confidence: 99%
“…The Arabidopsis AP2/ERF family comprises a large class of 144 transcription factors with diverse roles throughout the plant life cycle. The members of this class of regulatory proteins all contain the conserved AP2/ERF domain, a 60-70 amino acid region that is thought to mediate DNA binding and protein-protein interactions (Jofuku et al 1994;Okamura et al 1997). The AP2/ERF family has been organized into Wve phylogenetically distinct subfamilies that diVer in the number of AP2/ERF domains, as well as the amino acid similarity between these domains (Sakuma et al 2002).…”
Section: Introductionmentioning
confidence: 99%